Exercise-based gaming in patients with multiple sclerosis: A systematic review and meta-analysis - Amal Mohamed Elhusein; Hammad Ali Fadlalmola; Eltayeb Mohammed Awadalkareem; Ekram Yahia Mahmowd Alhusain; Soad Mohamed Alnassry; Mukhlid Alshammari; Elsadig Eltahir Abdulrahman; Doaa El Sayed Fadila; Fatma M. Ibrahim; Abdalrahman Abdallatif Mohmmed Saeed; Adel Abdalla; Hassan N Moafa; Ehab I. El-Amin; Daniel Mon Mamanao (Belitung Raya Foundation, Indonesia, 2024)
Background: Multiple sclerosis presents a significant burden, with balance disturbances impacting patients’ daily living. Conventional therapies have been supplemented with technological advancements like virtual reality (VR) and exergaming, providing engaging, multisensory rehabilitation options. Objective: This study aimed to synthesize evidence on exergaming’s role in multiple sclerosis treatment, particularly to evaluate the impact of exergaming on cognitive, motor, and psychological outcomes in patients with multiple sclerosis. Methods: A systematic review and subsequent meta-analysis design were employed. An extensive search was conducted up to June 2023 across five electronic databases - Web of Science, Scopus, PubMed, Cochrane, and EMBASE. The data extraction process from the selected studies was conducted independently. The risk of bias was assessed using the Cochrane Risk of Bias Assessment Tool 1 (ROB1) and the National Institutes of Health (NIH) assessment tool. Continuous outcomes were consolidated as mean differences (MD) with 95% confidence intervals (CIs). Meta-analyses were performed using RevMan ver. 5.4. Results: Out of 1,029 studies, 27 were included for meta-analysis. There were no significant differences in cognitive outcomes between the exergaming and the no-intervention group or the Conventional Physiotherapy and Rehabilitation interventions (CPRh) subgroups. However, the Symbol Digit Modalities Test (SDMT) showed a statistically significant difference in favor of exergaming in the no-intervention subgroup (MD = 5.40, 95% CI [0.08, 10.72], p = 0.05). In motor outcomes, exergaming only demonstrated better results in the 6-minute walking test compared to the no-intervention group (MD = 25.53, 95% CI [6.87, 44.19], p = 0.007). The Berg Balance Scale score in both studied subgroups and the Timed Up and Go (TUG) test in the no-intervention group favored exergaming. In terms of psychological outcomes, the Beck Depression Inventory did not reveal any significant differences, while the Modified Fatigue Impact Scale (MFIS) score favored exergaming in the CPRh subgroup. Conclusion: Exergaming shows promise for enhancing cognitive and motor functions, motivation, adherence, and quality of life in MS patients, which is beneficial for nurses. It can be tailored to individual preferences and easily conducted at home, potentially serving as a viable alternative to traditional rehab programs, especially during relapses. However, further research is necessary to fully understand its optimal and lasting benefits.